Neurite Branching Regulated by Neuronal Cell Surface Molecules in Caenorhabditis elegans - Jin, HoYong; Kim, Byunghyuk (Frontiers in Neuroanatomy, 2020)
The high synaptic density in the nervous system results from the ability of neurites to branch. Neuronal cell surface molecules play central roles during neurite branch formation. The underlying mechanisms of surface molecule activity have often been elucidated using invertebrates with simple nervous systems. Here, we review recent advances in understanding the molecular mechanisms of neurite branching in the nematode Caenorhabditis elegans. We discuss how cell surface receptor complexes link to and modulate actin dynamics to regulate dendritic and axonal branch formation. The mechanisms of neurite branching are often coupled with other neural circuit developmental processes, such as synapse formation and axon guidance, via the same cell-cell surface molecular interactions. We also cover ectopic and sex-specific neurite branching in C. elegans in an attempt to illustrate the importance of these studies in contributing to our understanding of conserved cell surface molecule regulation of neurite branch formation.